Efek Mediasi Pengetahuan Risiko pada Pengaruh Literasi Keuangan dan Perilaku Keuangan Terhadap Keputusan Pengambilan Kredit (Studi pada PT. Wom Finance Cabang Semarang) - Sitompul, Swito; Purnama, Eka Desy; Lumbantobing, Rudolf (Universitas Batanghari Jambi, 2024)
The purpose of this study was to analyze the mediating effect of risk knowledge on the effect of financial literacy and financial behavior on credit decision making (study at pt. wom finance Semarang branch). Quantitative research method with SmartPLS analyzer. Sample 100 people by distributing questionnaires. The results of literacy research did not prove the influence on credit decision making. Risk knowledge has a positive and significant effect on credit decision making. Increasing one's knowledge of risk, has an impact on increasing decisions to take credit. There is not enough evidence to state that Financial Behavior has a positive effect on Credit Decision Making. Financial Behavior has a positive and significant effect on Risk Knowledge.